2010
DOI: 10.1016/j.jenvrad.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Coupled radon, methane and nitrate sensors for large-scale assessment of groundwater discharge and non-point source pollution to coastal waters

Abstract: 1We constructed a survey system of radon/methane/nitrate/salinity to find sites of 2 submarine groundwater discharge (SGD) and groundwater nitrate input. We deployed 3 the system in Waquoit Bay and Boston Harbor, MA where we derived SGD rates using a 4 mass balance of radon with methane serving as a fine resolution qualitative indicator of 5 groundwater. In Waquoit Bay we identified several locations of enhanced groundwater 6 discharge, out of which two (Childs and Quashnet Rivers) were studied in more detail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 31 publications
6
61
0
1
Order By: Relevance
“…Specifically, water in the active layer (the surficial layer of the soil system above the permafrost that thaws every summer) could be transported into lakes and rivers during the thaw season (May−August) (10). Groundwater in some temperate climate regions can be highly enriched in methane (11), and groundwater discharge contributions to the methane budget of the coastal ocean and lakes in temperate climate have been reported (12,13). This conduit of methane transport may be particularly important in regions where organic-rich soils and anaerobic conditions promote methane production in the soil, such as in the Arctic (14).…”
mentioning
confidence: 99%
“…Specifically, water in the active layer (the surficial layer of the soil system above the permafrost that thaws every summer) could be transported into lakes and rivers during the thaw season (May−August) (10). Groundwater in some temperate climate regions can be highly enriched in methane (11), and groundwater discharge contributions to the methane budget of the coastal ocean and lakes in temperate climate have been reported (12,13). This conduit of methane transport may be particularly important in regions where organic-rich soils and anaerobic conditions promote methane production in the soil, such as in the Arctic (14).…”
mentioning
confidence: 99%
“…Of those new classes of sensors, most are focused on coastal areas because of higher power requirements, more onerous operation, maintenance, and calibration, as well as the higher signal-to-noise ratios present. Their use in the coastal ocean has increased dramatically in recent years from small process studies (e.g., Johnson and Coletti 2002;Sigleo et al 2005;Campbell et al 2013) to larger-scale use (e.g., Chavez et al 1997;Johnson et al 2009;Dulaiova et al 2010) because of both reduced sensor costs and a realization by nonscientific local ocean stakeholders that ocean biological and chemical information can be critical in decision making (Jannasch et al 2008;Ruhl et al 2011).…”
Section: A Relevant Global Observationsmentioning
confidence: 99%
“…They concluded that the data resolution increase as the water flow rates increase and the optimum water flow rate is 17 L min −1 . Dulaiova et al [6] replaced the RAD AQUA in Dulaiova et al [4] method with a membrane contactor (Liquicel, manufactured by Membrana) to eliminate the RAD AQUA response time to water 222 Rn concentration fluctuations.…”
Section: Introductionmentioning
confidence: 99%